Molecular theory of glyphosate adsorption to pH‑responsive polymer layers - Pérez Chávez, Néstor Ariel (2019)
By means of a molecular-level theory we investigate glyphosate adsorption from aqueous solutions to surface-grafted poly(allylamine) layers. Our molecular model of glyphosate and the polymeric material includes description of size, shape, conformational freedom, and state of protonation of both components. The composition of the bulk solution (pH, salt concentration and glyphosate concentration) plays a critical role to determine adsorption. Adsorption is a non-monotonic function of the solution pH, which can be explained in terms of the pH-dependent protonation behavior of both adsorbate and adsorbent material. Lowering the solution salinity is an efficient way to enhance glyphosate adsorption. This is because glyphosate and salt anions compete for adsorption to the polymer layer. In this competition, glyphosate deprotonation, to increase its negative charge upon entering the polymer layer, plays an critical role to favor its adsorption under a variety of solution conditions. This deprotonation is the result of the higher pH that establishes inside the polymer. Our results show that such pH increase can be controlled, while achieving significant glyphosate adsorption, through varying the grafting density of the material. This result is important since glyphosate degradation by microbial activity is pH-dependent. These polymeric systems are excellent candidates for the development functional materials that combine glyphosate sequestration and in situ biodegradation.